CHARACTERISTICS OF USING 3RD AND 4TH GENERATION CEPHALOSPORIN AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2021)
Objective: Describing characteristics of using 3rd and 4th generation Cephalosporin antibiotics at Thong Nhat Hospital in the period of 2019 - 2020.Subjects and methods: cross-sectional descriptive study on 158 medical records of patients discharged from hospital from February 20th, 2020 to February 24th, 2020 (5 days) was kept at themedical records store, Department of general planning, Thong Nhat hospital.Results: The majority of patients had no diagnosis of infection but had signs of infection, accounting for 69.92%. Duration of C3G/C4G antibiotic treatment of group with signs of infection was 9.22± 2.79 days. Cefotaxim was used the most, accounting for 26.58%. The majority of indications for the use of antibiotics C3G/C4G for patients were appropriate or partly appropriate, accounting for 74.05%. Efficiency of using appropriate or partially appropriate antibiotics had achieved high results, accounting for 39.24%. Most of the cases diagnosed or showed signs of infection after using antibiotics C3G/C4G obtained treatment efficacy, accounting for 75%. The majority of patients using C3G/C4G antibiotics achieved effectiveness in preventing wound infection in the patient with no signs of infection, accounting for 77.78%. The rate of elevated liver enzyme was 7.59%, the rate of thrombocytopenia was 3.16%.Conclusion: Duration of C3G/C4G antibiotic treatment of group with signs of infection was 9.22 ± 2.79 days. Cefotaxim were used the most. Most of indications to use antibiotics C3G/C4G were appropriate or partially appropriate. Efficiency of using appropriate or partially appropriate antibiotics had achieved high results. The rate of elevated liver enzyme was 7.59%, the rate of thrombocytopenia was 3.16%.
Keywords: Thong Nhat Hospital, 3rd and 4th generation Cephalosporin antibiotics